Zagadnienia funkcjonalności prawa rolnego w okresie transformacji gospodarki - Budzinowski, Roman (Wydział Prawa i Administracji UAM, 1995)
The purpose of the paper was to determine the functionality of agricultural law, i.e. finding an answer to the question whether the norms or institutions of that legal branch really serve the transformation of the economy, and whether they are - from that point of view - adequately functional. The transition from the centrally planned/directive system to a market economy system has resulted in far reaching changes in legal regulations relating to agriculture. The currently binding agricultural law is made up of many different legal acts; some issued as recently as in the last five years, some during the period of communist Poland and others date back to the period 1919 - 1939. First, detailed reference points are presented on the background of general assumptions of economic policy and assumptions and objectives of agricultural policy. Next, the development of agricultural structures and the infrastructure of the rural communities and agriculture is discussed. The conclusion of the paper is that legal instrumentalisation of the process of agricultural transformation is still in a formation phase. Many new legal acts need to be issued and the existing ones require amendments. Therefore, from the point of view of economic transformations, the agricultural law is not yet adequately functional.
Aspects of functionality of agricultural law during the period of economic transformations